1996
DOI: 10.1172/jci118645
|View full text |Cite
|
Sign up to set email alerts
|

Human fatty acid synthesis is stimulated by a eucaloric low fat, high carbohydrate diet.

Abstract: A new experimental approach was used to determine whether a eucaloric, low fat, high carbohydrate diet increases fatty acid synthesis. Normal volunteers consumed low fat liquid formula diets (10% of calories as fat and 75% as glucose polymers, n ϭ 7) or high fat diets (40% of calories as fat and 45% as glucose polymers, n ϭ 3) for 25 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
254
6
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(276 citation statements)
references
References 42 publications
14
254
6
2
Order By: Relevance
“…Results from both MIDA Hudgins et al, 1996;Neese et al, 1995;Faix et al, 1993;Hellerstein, 1995) and 2 H 2 O incorporation (Leitch & Jones, 1993;Jones et al, 1995) agree that hepatic DNL is a quantitatively minor pathway in men under conditions of a normal Western (high fat) diet. Calculated synthesis rate of palmitate or total non-essential FA based on¯ux through the circulating VLDL-TG pool is`1 ± 2 gad, a small amount compared to the 50 ± 150 g fat in the diet each day.…”
Section: Regulation Of Dnl In Humansmentioning
confidence: 88%
See 1 more Smart Citation
“…Results from both MIDA Hudgins et al, 1996;Neese et al, 1995;Faix et al, 1993;Hellerstein, 1995) and 2 H 2 O incorporation (Leitch & Jones, 1993;Jones et al, 1995) agree that hepatic DNL is a quantitatively minor pathway in men under conditions of a normal Western (high fat) diet. Calculated synthesis rate of palmitate or total non-essential FA based on¯ux through the circulating VLDL-TG pool is`1 ± 2 gad, a small amount compared to the 50 ± 150 g fat in the diet each day.…”
Section: Regulation Of Dnl In Humansmentioning
confidence: 88%
“…Nor do static changes in FA composition provide information about¯uxes through pathways; for example, DNLafat oxidation cycling could occur at a very high or a very low rate and remain consistent with these observations. Nevertheless, a similar principle (dilution of the essential FA linoleate in circulating lipids) has been used recently as a method for estimating rates of DNL (Petrek et al, 1997;Hudgins et al, 1996;see below).…”
Section: Comparison Of Fatty Acid (Fa) Composition In Adipose Tissue mentioning
confidence: 99%
“…Human clinical investigations have demonstrated that a diet low in fat and rich in carbohydrates (closely resembling the HCD used in our mouse study), even when administered for short periods of time, for example, 5 or 25 days, can lead to occurrence of uncomplicated fatty liver [12][13][14][15]. Thus, this mouse model is a highly relevant means of investigating mechanisms of hepatic steatosis.…”
Section: Introductionmentioning
confidence: 91%
“…After a single carbohydrate-rich meal only 1 ± 2% of the palmitate of the verylow-density-lipoprotein (VLDL) triacylglycerol-bound fatty acids (TGFAs) is derived from de novo synthesis (Hellerstein et al, 1991a,b). When eucaloric high-carbohydrate, low-fat diets are ingested, de novo lipogenesis is stimulated in human adults, but the rate of conversion of glucose to fatty acids remains low, in the order of 12 g triacylglycerol palmitate synthesized per day (Hudgins et al, 1996). It is of interest that fatty acid synthesis is less stimulated when starch or complex carbohydrates are substituted for simple sugars or short-chain glucose polymers (Hudgins, 1995).…”
mentioning
confidence: 99%
“…The effects of a high-CHO, lowfat diet on plasma lipid concentration (increased fasting plasma triacylglycerol, and decreased HDL-cholesterol concentrations) appear to be mainly mediated by increased sucrose and fructose intake (Coulston et al, 1983;Hudgins et al, 1995). The fatty acid preferentially formed by mammalian fatty acid synthase is the saturated fatty acid palmitate (16:0) (Hudgins et al, 1996). Therefore, when de novo lipogenesis is stimulated following ingestion of a high carbohydrate diet rich in sucrose and fructose, it would be important to know whether increased de novo synthesis of saturated fat contributes to the fatty acid patterns associated with an increased risk of cardiovascular disease.…”
mentioning
confidence: 99%